2023
DOI: 10.1093/nar/gkad017
|View full text |Cite
|
Sign up to set email alerts
|

The enterohemorrhagicEscherichia coliinsertion sequence-excision enhancer protein is a DNA polymerase with microhomology-mediated end-joining activity

Abstract: Bacterial genomes contain an abundance of transposable insertion sequence (IS) elements that are essential for genome evolution and fitness. Among them, IS629 is present in most strains of enterohemorrhagic Escherichia coli O157 and accounts for many polymorphisms associated with gene inactivation and/or genomic deletions. The excision of IS629 from the genome is promoted by IS-excision enhancer (IEE) protein. Despite IEE has been identified in the most pathogenic serotypes of E. coli, its biochemical features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 86 publications
1
25
1
Order By: Relevance
“…Indeed, as proposed from alignments with other members of this protein family (Calvo et al, 2023;Kusumoto et al, 2011; Figure 3),…”
Section: B I O Chemi C Al Analys Is Of Iee Ac Tivitie S: P Olymer a S...mentioning
confidence: 88%
See 4 more Smart Citations
“…Indeed, as proposed from alignments with other members of this protein family (Calvo et al, 2023;Kusumoto et al, 2011; Figure 3),…”
Section: B I O Chemi C Al Analys Is Of Iee Ac Tivitie S: P Olymer a S...mentioning
confidence: 88%
“…biochemical analyses using purified IEE demonstrated that the enzyme possesses DNA polymerase activity in the presence of Mg 2+ (Calvo et al, 2023) and can extend a 15 bp primer on a short 33 bp template using dNTPs but not NTPs (Figure 4ai). Mutation of two of the probable AEP catalytic residues (Figure 3), D142A/D144A, eliminated this activity.…”
Section: F I G U R E 2 a Histogram Showing The Frequency Of Excision ...mentioning
confidence: 99%
See 3 more Smart Citations